PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER BERBANTUAN CANVA UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMA MATERI DINAMIKA GERAK PARTIKEL - Raudatul Ardauyah; Muhammad Nasir; Muhammad Syafi'i (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The suboptimal cognitive learning outcomes of students in physics learning can be caused by many things, one of which is the teacher's inaccuracy in selecting learning models and media, which causes students to tend to be passive and does not achieve equitable student understanding in the class. One solution that can be done is the selection of models and media that place students as the center of learning. The purpose of this study was to determine the cognitive learning outcomes of grade XI students through the application of the Numbered Heads Together cooperative learning model assisted by Canva. The type of research used was a quasi-experimental research design with a nonequivalent post-test only control group design. The population of this study was grade XI students of SMA Negeri 4 Pekanbaru. The instruments and data collection techniques used a cognitive learning outcome test in the form of a post-test in the form of 20 objective questions. Data were analyzed using descriptive analysis and inferential analysis. The results showed a significant difference in student learning outcomes between the experimental class and the control class. The average cognitive learning outcome of students in the experimental class was 79.88 with a good category, while the average cognitive learning outcome of students in the control class was 68.49 with a sufficient category. This proves that the use of the Numbered Heads Together cooperative learning model assisted by Canva can improve students' cognitive learning outcomes in physics subjects.